Studies on Aluminium Uptake by the Seeds Under Different Chemical Milieu and Its Effect on Seed Germination and Plant Growth of Bengal Gram (Cicer arietinum), Pea (Pisum sativum) and Horse Gram (Dolichos biflorus) - Rao, T.V.R.K.; Kumari, Pallavi; Kanchan Mishra, Kumari (Asian Journal of Chemistry, 2011)
Aluminium uptake by the seeds of bengal gram (Cicer arietinum), pea (Pisum sativum) and horse gram (Dolicos biflorus) under different chemical milieu have been studied. Effect of aluminium absorption on the germination of seeds, as well as, the root and shoot length of the plants out of germinated seeds have also been studied. Effect of other cation viz., Ca2+ and anions viz., malate, tartarate and citrate on the aluminium absorption have also been studied. The seeds were also grown in earthen pots in soil cultures, with soils mixed with different aluminium ion concentration. The shoot length, number of leaves as well as nature of roots were observed after a definite time interval. Results revealed an expression of toxicity by the seeds upon exposure to the aluminium ions in solution of different concentrations. The germination was severely affected upon deep as well as shallow soaking of seeds in Al3+ solutions. Bengal gram germination was highly affected right from 100 ppm of Al3+ only. At 100 ppm of Al3+ it showed only 4 % germination, whereas pea and horse gram were relatively less affected by Al3+ toxicity. With increasing Al3+ concentration, all the three species of seeds increased Al uptake gradually. Comparative results of 24 and 48 h soaking time suggest that kinetically 24 h period seem to be sufficient time to express full toxicity and maximum Al3+ uptake. The plants germinated out of intoxicated seeds showed a depressed root and shoot length. Presence of Ca2+ or chelating anions like malate, tartarate and citrate could not alleviate aluminium toxicity to any significant extent for any of the seeds. In soil culture the Al toxicity was also expressed, however, to a lesser extent than that in solution intoxication. The morphogenic aspects such as shoot length and number of leaves were severely affected, particularly in case of horse gram, in soil culture.